Clinically unrecognized mitral regurgitation is prevalent in lone atrial fibrillation - Sharma, Sanjiv (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the prevalence of clinically unrecognized mitral regurgitation (MR) in lone atrial fibrillation (AF). METHODS: We studied the prevalence and severity of MR by transesophageal echocardiography (TEE) in patients with “lone” AF as compared to a matched cohort of patients in normal sinus rhythm (NSR) undergoing TEE for other indications besides recognized valvular heart disease. RESULTS: A total of 157 subjects (57 in the AF group and 100 in the NSR group) with structurally normal cardiac valves were included in the study. In the AF group, moderate MR or more was noted in 66% of the patients, mild MR in 18%, trace or no MR in 16%. In the control group, moderate MR was noted in 6% of patients, mild MR 31%, trace or no MR in 63 % of patients. Moderate MR or greater was significantly more prevalent in the AF group compared to the NSR group (66% vs 6%, P < 0.0001). CONCLUSION: Clinically unrecognized moderate MR is prevalent in “lone” AF -either as an etiologic factor leading to “lone” AF or developing after onset of AF.